The Determinants of Review Quality and Its Implication to Local Government’s Financial Statements Quality - Maulana, Aditya; Djamhuri, Ali; Purwanti, Lilik (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2017)
Abstract: The Determinants of Review Quality and Its Implication to Local Government’s Financial Statements Quality. This study aimed to explain the effect of competencies, organizational commitment and internal control system to the quality of the review and the implication to the quality of local government’s financial statements (LKPD). The review in this context is the review of LKPD. This research used multiple linear regression analysis to examine the effect of competencies, organizational commitment and internal control system to the quality of the review of LKPD, and the test to the effect of quality of the review on the quality of LKPD used simple linear regression analysis. Research objects are the internal auditor of the regional inspectorate on eight areas in ex-Malang residence. The results of the study indicate that the quality of the review affected by the competencies, organizational commitment and internal control system and quality of the review effect the quality of LKPD. Keywords: competencies, organizational commitment, internal control system, quality of the review, quality of local government’s financial statements.Abstrak: Determinan Kualitas Reviu dan Implikasinya terhadap Kualitas Laporan Keuangan Pemerintah Daerah. Penelitian ini bertujuan untuk menjelaskan pengaruh dari kompetensi, komitmen organisasi dan sistem pengendalian intern (SPI) terhadap kualitas reviu dan implikasinya terhadap kualitas Laporan Keuangan Pemerintah Daerah (LKPD). Reviu dalam hal ini adalah reviu LKPD. Penelitian ini menggunakan analisis regresi linier berganda untuk menguji pengaruh kompetensi, komitmen organisasi dan sistem pengendalian intern terhadap kualitas reviu, sedangkan uji terhadap pengaruh kualitas reviu terhadap kualitas LKPD menggunakan analisis regresi linier sederhana. Penelitian dilakukan terhadap aparat pengawas (auditor APIP) pada inspektorat daerah di 8 (delapan) wilayah eks Karesidenan Malang. Hasil penelitian membuktikan bahwa kualitas reviu dipengaruhi oleh kompetensi, komitmen organisasi dan sistem pengendalian intern dan kualitas reviu berpengaruh terhadap kualitas LKPD. Kata kunci: Kompetensi, komitmen organisasi, sistem pengendalian intern, kualitas reviu, kualitas LKPD.